Antenatal Care Practices: A Population-Based Multicenter Study from Saudi Arabia - Alqifari SF (Dove Medical Press, 2024)
Saleh F Alqifari Pharmacy Practice Department, Faculty of Pharmacy, University of Tabuk, Tabuk, 47512, Saudi ArabiaCorrespondence: Saleh F Alqifari, Pharmacy Practice Department, College of Pharmacy, University of Tabuk, Tabuk, Saudi Arabia, Tel +966532544334, Email salqifari@ut.edu.saBackground: Antenatal care (ANC) is the care women receive during pregnancy before birth and represents a cornerstone of maternal and child health. Previously, Saudi women faced various barriers to practicing ANC, including challenges related to transportation, low maternal education, poor communication with healthcare centers, and incorrect maternal beliefs. In line with Saudi Vision 2030, this multicenter cross-sectional study aimed to investigate the timing of ANC contact, coverage of service utilization in public hospitals among Saudi mothers, sociodemographic factors and antenatal health care utilization, and beliefs about prenatal vitamins, and supplement use among pregnant Saudi women.Methods: Data was collected from 1230 pregnant women across 11 Ministry of Health (MOH) facilities. The study assessed the timing of ANC initiation, beliefs about prenatal vitamins, and the use of folic acid, calcium, and iron during pregnancy. Chi-square tests were employed to analyze associations between variables.Results: The findings revealed that 14.55% of participants initiated ANC within the first 8 weeks of pregnancy, with 85.44% starting later. However, the majority 88.78% received prenatal care during pregnancy, regardless of the timing of ANC initiation. Beliefs about prenatal vitamins varied, with 20.08% agreeing that prenatal vitamins were only indicated for malnourished mothers, 72.35% disagreeing, and 7.56% uncertain. Moreover, 51.30% believed ANC should begin before pregnancy, 29.83% after pregnancy confirmation, and 13.57% during the first trimester, with no significant correlation between beliefs and ANC timing. Regarding prenatal care, 95.20% would recommend starting prenatal care with every pregnancy, regardless of the timing of their own ANC initiation.Conclusion: This study offers a comprehensive analysis of factors impacting late ANC contact and inadequate ANC contacts among pregnant Saudi women. These findings contribute to the broader understanding of ANC practices among Saudi women and underscore the importance of considering various determinants for tailored interventions and health education programs.Keywords: antenatal care, pregnancy complications, inadequate ANC, late ANC, prenatal care